The Analysis of Personal Writing in Freedom Writers Movie and Its Application in Teaching Writing - Hasanah, Uswatun; Chasanah, Zulia; Ngafif, Abdul (Linguistics and ELT Journal, 2025)
Personal writing, as depicted in the film “Freedom Writers,” offers valuable insights for writing instruction, particularly for students from diverse and challenging backgrounds. This study aims to investigate how personal writing activities—such as diaries and reflective journals—can be applied to foster self-expression, emotional growth, and identity development in the classroom. Using a qualitative descriptive approach, data were collected through content analysis of the movie and supported by relevant literature. The findings reveal that integrating personal writing into teaching not only enhances students’ motivation and writing abilities but also creates a more supportive and engaging learning environment. These results suggest that personal writing strategies can empower students, boost their confidence, and promote authentic written communication.